Enhancing Hospital Efficiency and Patient Outcomes Through Flexible Resident Scheduling: A Meta-Analysis - Dharmayuda, Cokorda Gde Oka; Arlina Dewi (Community Medicine and Education Journal, 2024)
The traditional, rigid work schedules of medical residents have been linked to fatigue, burnout, and potential adverse effects on patient safety. The implementation of flexible working hours has been proposed as a potential solution to mitigate these risks and improve patient outcomes. This meta-analysis aims to evaluate the impact of flexible resident scheduling on hospital efficiency, patient safety, and resident well-being. A systematic search of electronic databases (PubMed, Embase, Cochrane Library, Web of Science) was conducted to identify studies published between 2014 and 2024 that investigated the effects of flexible resident work hours on patient outcomes, medical errors, length of stay, and resident well-being. The quality of included studies was assessed, and data were extracted for meta-analysis using random-effects models. The meta-analysis included four studies. The results demonstrated that flexible resident scheduling was associated with a significant reduction in prolonged length of stay (pooled odds ratio [OR] = 1.10, 95% confidence interval [CI] = 1.06-1.14) and a decrease in medical errors (pooled OR = 0.93, 95% CI = 0.30-2.87). The results highlight the positive correlation between resident flexibility and enhanced patient care efficiency, indicating a decrease in medical errors. The findings of this meta-analysis suggest that implementing flexible resident scheduling can enhance hospital efficiency, improve patient outcomes, and promote resident well-being. Healthcare institutions should consider adopting flexible work-hour policies to optimize patient care and support the professional development of resident physicians.